Co-catalytic Fc/HGQs/Fe3O4 nanocomposite mediated enzyme-free electrochemical biosensor for ultrasensitive detection of MicroRNA. Issue 42 (27th April 2021) - Zhu, Liang; Zhang, Xiaolong; Chang, Yuanyuan; Xu, Sai; Yuan, Ruo; Chai, Yaqin
Abstract : A novel co-catalytic ferrocene/hemin/G-quadruplexes/Fe3 O4 nanoparticle (Fc/HGQs/Fe3 O4 ) was applied to construct ultrasensitive electrochemical biosensor through synergistic catalysis of hemin/G-quadruplexes (HGQs) and Fe3 O4 nanoparticles. Abstract : Herein, a novel co-catalytic ferrocene/hemin/G-quadruplexes/Fe3 O4 nanoparticles (Fc/HGQs/Fe3 O4 ) nanocomposite was synthesized to significantly magnify the electrochemical signal of ferrocene (Fc) using the synergistic catalysis of hemin/G-quadruplexes (HGQs) and Fe3 O4 nanoparticles as hydrogen peroxide enzyme mimics for the construction of ultrasensitive electrochemical biosensors. The fabricated electrochemical biosensor can achieve ultrasensitive detection of miRNA-155 ranging from 0.1 fM to 1 nM, as well as a limit of detection of 74.8 aM. This strategy provides a new route to exploring efficient signal labels for signal amplification and provides an impetus to find novel methods for the construction of biosensors for biological detection and the early clinic diagnosis of diseases.